Optimalisasi Indikator Program dalam Manajemen Strategi Pendidikan : Evaluasi, Implementasi, dan Dampaknya - Mardiyah Mardiyah; Vian Sabrina Herawati; Achmad Majidan Tanzihul Ali (Lembaga Pengembangan Kinerja Dosen, 2025)
Educational strategic management plays a crucial role in ensuring the effectiveness and efficiency of educational program implementation. One of the key aspects of this management is program indicators, which serve as measurement tools to assess the achievement of educational objectives. Program indicators in education can be classified into four main types: input, process, output, and outcome. Each of these indicators plays a distinct role in evaluating the success of an educational program. Additionally, effective indicators must meet the SMART (Specific, Measurable, Achievable, Relevant, Time-bound) criteria to be used effectively in planning and evaluation. This study aims to analyze the operational definition of program indicators in educational management, the types of indicators used, and the characteristics of effective indicators based on the SMART principle. A literature review method was employed by analyzing various relevant academic journals. The findings reveal that implementing clear and measurable program indicators enables educational institutions to continuously improve learning systems. Moreover, examples of program achievement indicators in education show that the success of a program can be systematically measured using a data-driven approach. With appropriate indicators, education management can more easily identify the strengths and weaknesses of a program and optimize strategies for implementing educational policies. The findings conclude that program indicators are a crucial component in enhancing education quality, particularly in resource management and assessing student learning outcomes.